Continuous Ethanol Fermentation in Immersed, Cross-Flow Microfiltration Membrane Bioreactor with Cell Retention - Olga Radočaj; Levente L. Diosady (Journal of Basic & Applied Sciences, 2014)
The key objective of this study was to devise a continuous ZeeWeed® membrane-based, immersed, microfiltration (MF) laboratory scale fermentation system for ethanol production with cell retention to achieve effective ethanol productivity, flux rates and sugar utilization. The new bioreactor was compared to the fermentation kinetics’ of the ultrafiltration unit.A synthetic glucose based medium was fermented by fresh, baker’s yeast to produce ethanol. The cells were not recycled; the medium was continuously withdrawn by filtration through an internal, immersed hollow-fiber cartridge. In this way, the inside of the membrane was exposed to the ethanolic solution, while broth with viable yeast cells remained outside the membrane. This design, with a cell retention system, provided much less membrane fouling (loss of about 76% of the original water flux after 96 hours of filtration) than while using the ultrafiltration (UF) external hollow-fiber membrane with cell recycling (loss of 97% of the original water flux after 2-3 hours of operation). Both modules converted at least 95% of glucose with biomass concentration of 30 g/L, and the final ethanol concentration of 62 g/L. However, the UF membrane became plugged after only 2 hrs of operation. The ZeeWeed® membrane operated successfully for 96 hrs with a final flux of 4 L/h m2 with ethanol concentration of 62.4 g/l, biomass yield 0.34 g/g and cell viability of 95.3%. This concept could be successfully used for biofuel production. A very strong positive correlation was observed between the biomass and EtOH concentration (R=0.98; at p<0.05).